2017
DOI: 10.1039/c6nj03353a
|View full text |Cite
|
Sign up to set email alerts
|

Core expanded, 21,23-dithiadiacenaphtho[1,2-c]porphyrin interactions with [60]fullerene

Abstract: Saddle-shaped 21,23-dithiadiacenaphtho[1,2-c]porphyrin exhibits binding interaction with [60]fullerene in addition to photon absorption bands extending to 1000 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In the search for new molecular architectures that act as hosts for fullerenes, researchers have focused on porphyrin-based systems. Although porphyrins are known to interact with fullerenes and cocrystallization adducts have been extensively reported, for a single porphyrin core, this interaction is usually too weak to be observed in solution. ,, Therefore, in order to achieve high affinity constants, the preparation of multiporphyrinic cages is required . Considerable efforts have been devoted to the tailoring of such complex systems to improve the interaction with fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for new molecular architectures that act as hosts for fullerenes, researchers have focused on porphyrin-based systems. Although porphyrins are known to interact with fullerenes and cocrystallization adducts have been extensively reported, for a single porphyrin core, this interaction is usually too weak to be observed in solution. ,, Therefore, in order to achieve high affinity constants, the preparation of multiporphyrinic cages is required . Considerable efforts have been devoted to the tailoring of such complex systems to improve the interaction with fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…Variously substituted acenaphthylene-fused dithiaporphyrins were reported by Hogan and Sutherland ( Scheme 304 ). 571 Thiophene building blocks were prepared by using the Hinsberg condensation between dimethyl 2,2′-thiodiacetate and acenaphthoquinone 304.1 to give the diester 304.2 , which was transformed into 304.5a – c in three steps. Condensation of these dicarbinols with pyrrole and the subsequent oxidation by DDQ afforded acenaphthylene-fused dithiaporphyrins, 304.6a – c .…”
Section: Macrocyclic Systemsmentioning
confidence: 99%
“… a Reagents and conditions: (a) (1) NaOMe, THF, (2) MeOH, H 2 SO 4 ; (b) LiAlH 4 , diethyl ether; (c) MnO 2 , DCM; (d) n -BuLi, TMEDA, 304.5a from 1-ethynyl-4-dodecyloxybenzene; 304.5b from 1-bromo-4-dodecyloxybenzene; 304.5c from ethynylbenzene; (e) (1) BF 3 ·Et 2 O, pyrrole, (2) DDQ. …”
Section: Macrocyclic Systemsmentioning
confidence: 99%
“…However, recently Bromby et al reported a series of novel N 2 S 2 porphyrins with meso‐phenyl substituted long alkoxy groups that shows interesting optical and electrical properties and could behave as ambipolar materials for organic electronic devices [ 19–22 ] . However, to the best of our knowledge, there are only one reports of self‐assembled 21,23‐dithiaporphyrin having decyl or dodecyl chains that shows columnar liquid crystalline phases (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…[17] Nowak-Kr ol et al mentioned N 4 systems with 12 long alkyloxy groups showing low melting point and showed that the melting point of octyloxy derivative is 55.1 C that is comparable with the porphyrin 3 (54.5 C) with N 2 S 2 system reported in this article. [18] However, recently Bromby et al reported a series of novel N 2 S 2 porphyrins with meso-phenyl substituted long alkoxy groups that shows interesting optical and electrical properties and could behave as ambipolar materials for organic electronic devices [19][20][21][22] . However, to the best of our knowledge, there are only one reports of selfassembled 21,23-dithiaporphyrin having decyl or dodecyl chains that shows columnar liquid crystalline phases (Figure 2).…”
Section: Introductionmentioning
confidence: 99%